Report of erucism caused by Automeris egeus Cramer (Lepidoptera: Saturniidae) and a brief update on caterpillar envenomation in Brazil - Citeli, Nathalie Kaladinsky; Queiroz, Pedro Paulo de; de-Carvalho, Mariana; Lepesqueur, Cintia; Corrêa, Bruno Alessandro Augusto Peña; Meneses, Afonso Santiago Oliveira (EntomoBrasilis, 2021)
We report a case of erucism provoked by the Automeris egeus Cramer caterpillar and update the distribution of caterpillar poisoning in Brazil, showing the regions with the highest incidence rates. We also correlated the incidence rate with anthropic impact rates in all Brazilian municipalities, taking as a reference the Human Footprint Index. The victim presented erucism, burning pain, itching, and local hyperthermia. The highest incidence rates were in southern Brazil. We suggest including A. egeus in the Brazilian list of animals with medical importance, and that Brazilian Ministry of Health indicates the genus of the animals involved in envenomation events on its platform.